AN INVESTIGATION INTO THE KEY DRIVERS OF CUSTOMER CARE AND LOYALTY IN THE COMMERCIAL BANKING SECTOR (NAMIBIA) (Singaporean Journal of Business Economics and Management, 2015)
Customer care and ultimately customer satisfaction have become so vital and significant in business–to-customer (B2C) types of environment. Many a times, satisfying customers can be quite an issue owing to the fact that in such environments it may be difficult to perceive exactly what goes on in a customer’s mind. Regardless of the numerous studies piloted on the characteristics of banking service quality as perceived by customers, such perceptions till today remain enigmatic. Hence it becomes a challenge for service providers that place strong emphasis on customer relations, to either to meet or exceed the targeted customers’ level of satisfaction as expected by them. With this increasing emphasis on service delight and quality, the banking industry in Namibia has become increasingly competitive and a natural dilemma. This study therefore attempts to investigate the key drivers of loyalty and customer care in the commercial banking sector